The seasonality of reproduction in photoperiod responsive and nonresponsive northern red-backed voles (Myodes rutilus) in Alaska - Stevenson, K.T.; van Tets, I.G.; Nay, L.A.I. (Canadian Journal of Zoology, 2009)
High-latitude arvicoline rodents usually reproduce in warmer months, but winter breeding has been documented in several species, including the northern red-backed vole ( Myodes rutilus (Pallas, 1779) Wilson and Reader, 2005; formerly Clethrionomys rutilus (Pallas, 1779)). We tested whether the reproductive condition of the species is linked to changes in environmental parameters or its body condition, and we tested the frequencies at which different reproductive phenotypes are exhibited under field and laboratory conditions. Free-living voles in south-central Alaska reached peak reproductive organ masses in spring (females) and early summer (males). Between-subject comparisons showed an effect of body mass, photoperiod, percent fat, temperature, and snow depth on reproductive organ masses, depending on the sex and breeding period (p < 0.05). One instance of late-summer photoperiod nonresponsiveness was observed, but we detected no winter breeding. Captive male voles given food ad libitum and housed at room temperature exhibited strong phenotypic variation in testis mass in response to short photoperiods. The percentage of nonresponders was 28.2% and was within the known range of nonresponsiveness for lower latitude species (20%–40%). Thus, photoperiod nonresponsive morphs are conserved in at least one arctic and subarctic species at frequencies comparable to lower latitude voles despite no observance of winter breeding in the field. Voles exhibit reproductive elasticity and may breed in winter if environmental conditions enable them.